A simple and dual responsive efficient new Schiff base chemoreceptor for selective sensing of F− and Hg2+: application to bioimaging in living cells and mimicking of molecular logic gates1. Issue 76 (19th August 2015) - Chowdhury, Additi Roy; Ghosh, Pritam; Roy, Biswajit Gopal; Mukhopadhyay, Subhra Kanti; Mitra, Partha; Banerjee, Priyabrata
<x xml:space="preserve">Abstract</x> A novel colorimetric hydrazine-functionalized Schiff base chemoreceptor, NPMP, was synthesized following a simple one-step Schiff base condensation pathway.